An Analysis of Germanium–Silicon/Silicon Strained Superlattice Structure Using Convergent Beam Electron Diffraction. (28th January 2016) - Mogili, N. V. V.; Tanner, D. A.; Nakahara, S.
Abstract: Strained superlattices (SSLs) are typically found inside the p‐n junction area of semiconductor devices and consist of very thin alternating layers of different material. There exists a small lattice mismatch between these materials which results in localised strain, as in the case of germanium‐silicon/silicon SSLs. Strain measurements using a convergent beam electron diffraction (CBED) technique inside a transmission electron microscope (TEM) have indicated that the strain measured normal to these germanium–silicon/silicon SSLs varies almost sinusoidally, in spite of theoretical predictions which indicate a much sharper change in strain between these layers. A theoretical formulation involving an elasticity solution has been developed to predict the strain inside these SSL structures. The comparison of theoretical and experimental results clearly quantifies the effect of beam size on the spatial resolution of CBED measurements. Given that beam size is critically dependent on the spot size of the beam, the convergence angle, the specimen thickness and the position of the focused plane, these parameters are all clearly accounted for in the theoretical predictions.